A long-lived planetesimal dynamo powered by core crystallization - Maurel, C; Bryson, JFJ; Shah, J; Chopdekar, RV; Elkins-Tanton, LT; Raymond, CA; Weiss, BP (Wiley, 2021)
The existence of numerous iron meteorite groups indicates that some planetesimals underwent melting that led to metal‐silicate segregation, sometimes producing metallic cores. Meteorite paleomagnetic records suggest that crystallization of these cores generated dynamo magnetic fields. Here we describe the magnetic history of the partially differentiated IIE iron meteorite parent body. This is the first planetesimal for which we have a time‐resolved paleomagnetic record constrained by 40Ar/39Ar chronometry spanning several tens of million years (Ma). We find that the core of the IIE parent body generated a dynamo, likely powered by core crystallization, starting before 78 ± 13 Ma after solar system formation and lasting at least 80 Ma. Such extended core crystallization suggests that the core composed a substantial fraction of the body ( >~ 13%–19% core‐to‐body radius ratio depending on the body’s radius), indicating efficient core formation within some partially differentiated planetesimals.